Marketing Strategy Through Instagram and TikTok Promotion Based on the SOAR Analysis: A Case Study of Gocah Coffee in Medan (Pusat Riset dan Inovasi Nasional, 2026)
The rapid expansion of the food and beverage (F&B) industry in Indonesia particularly the growth of local coffee shops illustrates a shifting consumer landscape in which coffee has evolved from a basic beverage into a lifestyle product. Gocah Coffee, established in 2024 in Medan, adopts Instagram and TikTok as its primary digital marketing channels to strengthen brand visibility and attract younger consumers. However, the performance of its digital promotion has been inconsistent, especially regarding content reach, engagement, and conversion into offline customer visits. This study aims to formulate an effective digital marketing strategy for Gocah Coffee using the SOAR (Strengths, Opportunities, Aspirations, Results) framework. A descriptive qualitative case study approach was employed, involving 13 informants consisting of owners, employees, and customers, supplemented by direct observation of social media activities and documentation of content insights. The findings indicate that Gocah Coffee possesses strong visual identity, appealing store ambience, and increasing content quality. Opportunities include leveraging TikTok’s algorithmic trends, encouraging user-generated content, and optimizing insight-based content planning. The aspirations of the business emphasize stronger brand awareness, consistent posting behavior, and the development of a loyal community. The targeted results involve boosting engagement rates, follower growth, and in-store foot traffic. This study proposes a SOAR based digital marketing strategy that is actionable, scalable, and relevant for F&B MSMEs seeking to compete in a digitally driven market environment.